CAR T-cell therapy in autoimmune diseases - Schett, Georg; Mackensen, Andreas; Mougiakakos, Dimitrios (Lancet, 2023)
Despite the tremendous progress in the clinical management of autoimmune diseases, many patients do not respond to the currently used treatments. Autoreactive B cells play a key role in the pathogenesis of autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis, and multiple sclerosis. B-cell-depleting monoclonal antibodies, such as rituximab, have poor therapeutic efficacy in autoimmune diseases, mainly due to the persistence of autoreactive B cells in lymphatic organs and inflamed tissues. The adoptive transfer of T cells engineered to target tumour cells via chimeric antigen receptors (CARs) has emerged as an effective treatment modality in B-cell malignancies. In the last 2 years treatment with autologous CAR T cells directed against the CD19 antigen has been introduced in therapy of autoimmune disease. CD19 CAR T cells induced a rapid and sustained depletion of circulating B cells, as well as in a complete clinical and serological remission of refractory systemic lupus erythematosus and dermatomyositis. In this paper, we discuss the evolving strategies for targeting autoreactive B cells via CAR T cells, which might be used for targeted therapy in autoimmune diseases.
CRIS-Team Scopus Importer:2023-10-13